TEXT, CONTEXT AND CULTURAL LACUNAE: TIME AND MEANINGS - E. M. Maslennikova (Концепт: философия, религия, культура, 2019)
A literary text is the reflection of dominant values existing in the society. Within the semantic space of the text, readers are trying to find their self-determination. Translation is considered as a bilingual text communication. The translating process is guided by the set of interpreters' value orientations and their vision of the text with reference to the current (actual) and / or modern communicative situation. The translated text as a target secondary text is to replace the original source text in the host language and culture system. There are special relationships between the translation and the original as they are (quasi-)identical. Their adequacy or equivalence depends on the amount and quality of the information transmitted in the secondary text in comparison with the source text. In addition to purely linguistic barriers (different language systems and rules), the author, the translator and the secondary reader are divided by textual gaps (lacunae) caused by text peculiarities. Text peculiarities are influenced by its content, form, poetics and techniques, genre and readers for which the text is intended. Temporal parameters of the author's code can make the text for the next generation of readers either a closed text in the form of a-text-not-for-all, or a semi-closed text that requires proper comments. The article deals with complexities of bilingual cross-cultural text communication arising because of discrepancies in behavioural norms, non-verbal means of communication, artistic perception of the world and national characters. Such discrepancies turn out a source of cultural lacunae not only for interpreters who act as primary readers, but also for secondary readers from the host language and culture system. The article is based on six English translations of M.A. Bulgakov's novel "The Master and Margarita".